Experience of Use of Advanced Communication Systems and Distance Learning To Support Teaching at Politecnico Di Torino - Belingardi, Giovanni; Obradovic, Jovan (International Journal of Industrial Engineering and Management, 2011)
Nowadays the possibilities for teaching and education are offered by the use of information and communication technologies (ICT) and e-learning systems. The implementation of these systems offers also new insight into subjects that are not possible with traditional methods. Also, it will improve, supplement and aid traditional teaching methods and will also enable the beginning of different teaching and learning processes that are less limited in space and time. It is presented the use of high technology communication systems at Politecnico di Torino, implemented with the purpose of improved university education. Also, the multidisciplinary working systems, communication models, multimedia and video production, videoconferencing systems and special services for disabled, are briefly described. The Centre for e-learning and multimedia (CeLM) at Politecnico di Torino aims to be the institutional reference for the coordination of support activities in the area of technology and multimedia training. The Centre puts the particular emphasis on skills in e-learning and open and distance learning and on the activities related to the release and testing of multimedia technologies. Article history: Received (17.05.2011); Revised (21.09.2011); Accepted (28.10.2011)